Printability Properties of Some Alkaline Sulfite-Anthraquinone-Methanol Handsheets - Mertoglu Elmas, Gulnur; Sonmez, Sinan (Asian Journal of Chemistry, 2011)
Alkaline sulfite-anthraquinone-methanol, an organosolv pulp production method, is an environmentally friendly method. Alkaline sulfite-anthraquinone-methanol pulps are produced from fast growing Samsun poplar clone (P. deltoides) and grown in Istanbul, Robinia pseudoacacia and Pinus pinaster grown in Turkey as a raw material. In this study, alkaline sulfite-anthraquinonemethanol pulps were used to make hand-sheets. Then, the optical and printability properties of alkaline sulfite-anthraquinone-methanol hand-sheets were compared. It was found that the use of Samsun poplar clone in making hand-sheets resulted in decrease surface roughness and increase brightness, gloss and opacity. In addition, it had the highest print optical density and print chroma. Although the use of Robinia pseudoacacia in making hand-sheets decreased print mottle, Pinus pinaster increased print mottle. However, Pinus pinaster had the highest delta gloss. The Samsun p. clone provided the best print contrast which is beneficial to print readability.